Comparative genome and metabolome analyses uncover the evolution and flavonoid biosynthesis between Apocynum venetum and Apocynum hendersonii - Gang Gao; Aminu Shehu Abubakar; Jikang Chen; Ping Chen; Kunmei Chen; Chunming Yu; Xiaofei Wang; Xiaojun Qiu; Xiaoyu Huang; Deyi Shao; Yue Wang; Yu Chen; et al. (iScience, 2023)
Summary: Apocynum species have great application prospects in textile and phytoremediation of saline soil, are rich in flavonoids, and possess medicinal significance. Here, we report the draft genomes of Apocynum venetum and Apocynum hendersonii, and elucidate their evolutionary relationship. The high synteny and collinearity between the two suggested that they have experienced the same WGD event. Comparative analysis revealed that flavone 3-hydroxylase (ApF3H) and differentially evolved flavonoid 3-O-glucosyl transferase (ApUFGT) genes are critical for determining natural variation in flavonoid biosynthesis between the species. Overexpression of ApF3H-1 enhanced the total flavonoid content and promoted the antioxidant capacity of transformed plants compared to the wild-type. ApUFGT5 and 6 explained the diversification of flavonoids or their derivatives. These data provide biochemical insight and knowledge on the genetic regulation of flavonoid biosynthesis, supporting the adoption of these genes in breeding programs aimed at the multipurpose utilization of the plants.